2020
DOI: 10.1186/s13063-020-04320-3
|View full text |Cite
|
Sign up to set email alerts
|

Is natural (6S)-5-methyltetrahydrofolic acid as effective as synthetic folic acid in increasing serum and red blood cell folate concentrations during pregnancy? A proof-of-concept pilot study

Abstract: Background: North American health authorities recommend 0.4 mg/day folic acid before conception and throughout pregnancy to reduce the risk of neural tube defects. Folic acid is a synthetic form of folate that must be reduced by dihydrofolate reductase and then further metabolized. Recent evidence suggests that the maximal capacity for this process is limited and unmetabolized folic acid has been detected in the circulation. The biological effects of unmetabolized folic acid are unknown. A natural form of fola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Pregnant dams ( n = 16–18/group) received an isocaloric AIN-93G diet (energy density 4.0 kcal/g) [ 33 ] containing either the recommended (1X, 2 mg/kg diet, control) or 5X-quantity of FA for rodents (1X-FA or 5X-FA) or equimolar recommended levels of [6 S ]-5-methyltetrahydrofolic acid, calcium salt (1X, 2.1 mg/kg diet, Metafolin ® , Merck & Cie, Schaffhausen, Switzerland) or 5X-quantity of MTHF (1X-MTHF or 5X-MTHF). FA and MTHF diets at equimolar doses have been used in clinical trials assessing folate status and related-health effects [ 34 , 35 , 36 ]. The recommended (1X) dose was chosen based on the FA requirements for rodents for adequate growth rate [ 37 ] and reflects the FDA requirements for non-pregnant women (400 µg/day) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pregnant dams ( n = 16–18/group) received an isocaloric AIN-93G diet (energy density 4.0 kcal/g) [ 33 ] containing either the recommended (1X, 2 mg/kg diet, control) or 5X-quantity of FA for rodents (1X-FA or 5X-FA) or equimolar recommended levels of [6 S ]-5-methyltetrahydrofolic acid, calcium salt (1X, 2.1 mg/kg diet, Metafolin ® , Merck & Cie, Schaffhausen, Switzerland) or 5X-quantity of MTHF (1X-MTHF or 5X-MTHF). FA and MTHF diets at equimolar doses have been used in clinical trials assessing folate status and related-health effects [ 34 , 35 , 36 ]. The recommended (1X) dose was chosen based on the FA requirements for rodents for adequate growth rate [ 37 ] and reflects the FDA requirements for non-pregnant women (400 µg/day) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency and safety of 5-MTHF has been established, including in children [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and has been demonstrated to be at least as efficient as FA in reducing homocysteine levels in healthy women [ 38 , 39 ]. It is effective in reducing Hcy in men and women of reproductive age who are carriers of the MTHFR T677T variant [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. 5-methylTHF can/could effectively prevent NTDs by improving folate biomarkers in young women during early pregnancy [ 33 ].…”
Section: Folate Malabsorptionmentioning
confidence: 99%
“…In order to prevent NTDs, nutritional supplementation with 5-MTHF can effectively improve folate biomarkers in young women during early pregnancy [ 31 , 34 , 35 ]. In adults, C677T SNP is a hazard for spermatogenesis [ 46 ], and FA supplementation has been clearly demonstrated as an exacerbating factor in men carrying this SNP [ 47 ], for whom the methylome is already compromised.…”
Section: Folate Malabsorptionmentioning
confidence: 99%
“…Folate is a generic term for vitamin B9 that includes several forms, including that naturally found in food (natural folate). All folate forms have a common structure but differ based on the pteridine ring and whether it is reduced or oxidized [23]. Folate derived from food such as leafy green vegetables are polyglutamates (Figure 1), whereas synthetic FA is a monoglutamate (Figure 2) [21].…”
Section: Folate Metabolismmentioning
confidence: 99%
“…One small study showed that the majority of FA (at a physiologic dose) passes into the portal vein in an unmodified form, whilst monoglutamates are almost all converted to 5-MTHF [31]. All forms of folate must be converted to 5-methyltetrahydrofolate (5-MTHF), which is the main form of folate found in plasma, accounting for approximately 98% of total serum folate [16,23]. Where natural folates can be converted directly to 5-MTHF directly, FA relies on the dihydrofolate reductase (DHFR) enzyme to be reduced [21,24].…”
Section: Folate Metabolismmentioning
confidence: 99%